(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This paper aims at studying the link in leadership and competency mapping in private banks. Competencies are parts of a work which are reflected in conduct that is clear in a work place. The regular component most often referenced are information, abilities, capacities, aptitudes, individual appropriateness conduct and effect on execution at work. The principle accentuation of associations has started to have faith in dominating and not in contending. The competency mapping influences the current competencies of workers. Information for the examination was gathered from 120 workers by random sampling method and an all-around characterized questionnaire was set up with 3 point likert scale and dispersed among the representatives.